The Role of «Muntahab Ut-Tavorikhi Mu'ini» and the Works of Russian Temurist Scientists in Studying the Military Art of the Time of Amir Timur and the Timurians (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article provides information about the military management system of Amir Temur in Mu'iniddin Natanzi's «Muntahab ut-Tavarikhi Mu'ini» and scientific research works, treatises, and scientific-literary publications conducted by Russian Temur scientists. At the same time, in the following years, special attention was paid to the issues of truthful coverage of Amir Temur's personality.